Shareholder Rights, Boards, and CEO Compensation - Fahlenbrach, Rüdiger (Review of Finance, 2009)
Abstract I analyze the role of executive compensation in corporate governance. As proxies for corporate governance, I use board size, board independence, CEO-chair duality, institutional ownership concentration, CEO tenure, and an index of shareholder rights. The results from a broad cross-section of large U.S. public firms are inconsistent with recent claims that entrenched managers design their own compensation contracts. The interactions of the corporate governance mechanisms with total pay-for-performance and excess compensation can be explained by governance substitution. If a firm has generally weaker governance, the compensation contract helps better align the interests of shareholders and the CEO.